Mpox Virus: Control of In-Hospital Occupational Transmission Experience from a Tertiary Level Hospital in Milan, Italy - Raccagni, Angelo Roberto; Gianotti, Nicola; Moro, Matteo; Mileto, Davide; Gordo Perez, Victoria; Castagna, Antonella; Nozza, Silvia (Life (Basel, Switzerland), 2023)
Mpox has caused a global outbreak since May 2022, particularly affecting people belonging to key populations, but cases among healthcare providers have been reported. The aim of this work is to present the experience of the Infectious Diseases Unit of San Raffaele Scientific Institute, Milan, Italy with respect to infection control and prevention of mpox occupational transmission. Between May–November 2022, 140 individuals were diagnosed with mpox and six required hospitalization. Overall, 12 medical doctors and 22 nurses provided care to people with mpox. A hospital policy aimed at controlling viral transmission was implemented in May 2022. Protective equipment was used for all healthcare providers. One accidental puncture occurred with a scalpel contaminated with blood from a mpox viremic individual (mpox plasma cycle threshold = 36); no mpox related symptoms were observed and mpox testing ruled out transmission. Six months following exposure, neutralizing antibodies were not detectable, ruling out contagion. Overall, we observed no mpox transmission among healthcare workers, despite the number of visits and procedures performed, including bodily-fluids sampling, and even following puncture with contaminated blood. Hospital preparedness for the management of new infectious disease outbreaks, with rapid implementation of policies aimed at controlling infection, is paramount to avoid occupational transmission.